PENGARUH PERTUMBUHAN EKONOMI, PENGGANGURAN, DAN KEMISKINAN TERHADAP KINERJA KEUANGAN DAERAH (Studi Kasus di Wilayah Soloraya Periode 2013 – 2015) - Antonius Krisna Yoga Raharja, Suharno & Fadjar Harimurti (Universitas Slamet Riyadi, 2017)
High economic growth, decreasing unemployment and poverty is a picture ofthe results of government performance in the welfare of its people. Financialperformance is increasing, allegedly not always capable of encouraging economicgrowth, and reduce unemployment and poverty. The purpose of this study todetermine the effect on the financial performance of economic growth,unemployment and poverty. This study used a sample of six counties and one city inCentral Java province with the object of research is the performance of the financial,economic growth, unemployment and poverty in 2013 – 2015. Testing the hypothesisin this study was conducted with the assumption of classical and multiple linearregression analysis. Based on budget data description District / Municipality in thearea Soloraya known that economic growth is the highest budget of 6,71% which isin Sragen in 2013. While the lowest budget growth is 4,79% which is in Wonogiri in2013. Berdasarkan acquire data budget District / Municipality in the area Solorayaknown that unemployment is the highest budget by 7,22%, ie in Surakarta in 2013.While unemployment is the lowest budget of 2,03% which is in Boyolali in 2015.Based on data description budget data District / Municipality in Soloraya regionknown that most poverty budget is 15,93% which is in Sragen in 2013. While thelowest budget of poverty is 9,18% which is in Sukoharjo district in 2013.Keywords: financial performance, economic growth, unemployment, poverty